Disaggregated Sales and Stock Returns - Agarwal, Sumit; Qian, Wenlan; Zou, Xin (Management Science, 2021)
Using transaction-level credit-card spending from a large U.S. financial institution, we show that disaggregated sales provide accurate and persistent signals of customer demand relevant to a firm’s stock pricing. After controlling for earnings and sales surprises, one interquintile increase in the adjusted customer spending during a firm’s fiscal quarter leads to a 1.5 percentage point increase in the 60-day post–earnings announcement cumulative abnormal return. The predictability concentrates in consumer-oriented firms, especially those relying more on indirect sales distribution channels. We also find a stronger return response to spending from high-FICO-score, high-liquidity, and loyal customers. The transmission speed of disaggregated sales information is slower than that of the earnings information, and small firms or firms far from their end customers exhibit a more delayed price response. Finally, the return implications of adjusted customer spending extend to firms along the production chain. This paper was accepted by Haoxiang Zhu, finance.